Urine culture pattern in Norvic International Hospital - Jha, R; Sijapati, K; Pant, AD (Journal of Institute of Medicine Nepal, 2008)
Background: Urinary tract infections are responsible for considerable morbidity particularly in sexually active women. The aim of this study was to study the distribution of age and sex for significant growths isolated in urine specimens, the microorganisms associated and their sensitivity pattern to antibiotics Methods: Data on age, sex, organism isolated and sensitivity pattern was collected for all (total 103) culture positive urine samples sent between Baisakh 2064 to Bhadra 2064. Results: Majority of patients were females and most were between 20-39 years of age. E. coli was the most common organism isolated ( 81.6%) followed by Proteus (16.5%). E coli showed sensitivity to cefotaxime, ceftriaxone and cefexime in most cases. Conclusion: Females in sexually active age group show significant bacterial growth in urine more frequently than males . E coli are the commonest pathogen isolated. Key words: Antibiotic sensitivity, urine culture, urinary tract infection The full text of this paper is available at Journal of Institute of Medicine website